FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUTUSAN PETANI BERALIH KEMITRAAN DALAM BERUSAHATANI : KASUS PETANI KEMITRAAN TEBU DI PT GUNUNG MADU PLANTATAIONS BERALIH KE KEMITRAAN UBI KAYU DI PABRIK BUMI WARAS - Agiesta, Via; Widjaya, Sudarma; Hasanuddin, Tubagus (Lampung University, 2017)
This study aims to determine the performance of partnership patterns of cassava farming in Plant Earth Sane, factors associated with the decision-making of farmers switching partnership from cane farming to cassava farming, and a comparison between cassava farming income and cane farming income. The survey method was conducted in Central Lampung regency by interviewing 21 cassava farmers chosen purposively as respondents. Data were collected in December 2015 to May 2016 and analyzed using Kendall Partial Analysis. The results showed that the performance of cassava farming partnership system are at a very adequate classification in terms of financial aid, processing yields, profit-sharing system, the requirements of the partnership, and farming income. Farmers’ decisions to switch partnership from cane farming to cassava farming were determined by technical factors of cultivation, social pressures, marketing of the crop, profit-sharing system, capital aid, the requirements of the partnership, farm income, the distance from farming land to cassava processing factory, and the desire of farmers to cultivate their own land. Cassava farming income per ha/season is Rp13,282,985.13 with R/C of 2.15, greater than those of sugarcane farming with income of Rp11,403,828.63 and R/C of 2.13.Key words : cassava, farm, partnership, sugarcane